Early benefit assessment of new drugs in Germany: Framework for submission of dossiers by pharmaceutical companies. (1st September 2013) - McGauran, Natalie; Köhler, Michael; Todd, Michael
Abstract : For the early benefit assessment of new drugs in Germany, medical writers are involved in the preparation of dossiers submitted by pharmaceutical companies to the main decision-making body of the German statutory healthcare system, the Federal Joint Committee ( Gemeinsamer Bundesausschuss, G-BA). These dossiers are generally assessed by the Institute for Quality and Efficiency in Health Care ( Institut für Qualität und Wirtschaftlichkeit im Gesundheitswesen, IQWiG). The present article summarises the documents that are publicly available to guide dossier preparation and to ensure transparency. These documents detail the requirements for the structure and content of the dossier, procedures for dossier submission, assessment by IQWiG, and decision-making by the G-BA. Medical writers should adhere closely to the available guidance to help ensure that the submitted dossiers fulfil the formal and content requirements.